Chapter Significant Geographies in The Shadow Lines - Orsini, Francesca (University of Turin, 2020)
Approaches to world literature often think through binaries of local/global, major/minor, provincial/cosmopolitan, taking them as given positions on a single world map. To an extent, this is true of Amitav Ghosh's prize-winning essay "The testimony of my grandfather's bookcase" (1998), which reflects on his grandfather's collection of world literature books to think about the relationship between his grandfather's provincial location in Calcutta and the world. Yet in The Shadow Lines Ghosh takes a much more complex and interesting approach to space, the world, perception and narration. In the novel's complex narration, space, time, and self always appeared mirrored through other people, times, and spaces. Places also acquire reality and meaning only after they are first narrated and imagined, often several times, and before they are experienced directly. This is a stance that has deep existential but also epistemological implications that go beyond "simply" critiquing colonial and national border-making. This essay explores how (and which) spaces become "significant" in the novel, and how the novel's approach to space can be productive for thinking about world literature.